4B.10: 24 HOUR URINE FREE CORTISOL TO CORTISONE RATIO IS A NOVEL BIOMARKER FOR INCREASED LEFT VENTRICULAR MASS IN DIABETIC HYPERTENSIVES. (June 2015) - Tang, J.; Tavintharan, S.; Sum, C.; Lim, S.; Ong, H.
Abstract : Objective: Renal 11 beta hydroxysteroid dehydrogenase type 2 (11BHSD2) is a key molecular player in the renin- angiotensin- aldosterone system (RAAS). We hypothesize that decreased renal 11BHSD2 activity, as measured by increased urinary free cortisol to cortisone (UFF/UFE) ratio using gas chromatography-mass spectrometry (GCMS), may be an important biomarker in identifying diabetic patients with increased left ventricular mass. Design and method: We studied insulin-naive male patients with type 2 diabetes and stage 1 hypertension (blood pressure of 140–160/90–100 mmHg) in this study. 24-hour urine was collected and UFF/UFE ratio was determined using GCMS. All patients underwent 2D-echocardiogram (2DE) for measurement of left ventricular mass index (LVMI). Results: A total of 43 diabetic male patients with hypertension were evaluated in this study. As per current hypertension guidelines, all subjects were already taking either an angiotensin converting enzyme inhibitor (ACE) or angiotensin receptor blocker (ARB) for their hypertension control. The mean 24 hour UFF/UFE ratio was 0.77+/- 0.05 (interquartile range 0.52 to 1.00), with higher UFF/UFE ratios reflecting lower renal 11BHSD2 activity. Higher UFF/UFE ratio correlated with higher LVMI (r = 0.46, p = 0.003). Among the subjects in the highest quartile (UFF/UFE ratio > 1.00), the left ventricular mass index was significantly higher (113.8 g/m2 vs 89.1 g/m2, p = 0.03; difference between means 23.7 +/- 9.8 g/m2) when compared to the rest of the cohort. This association was independent of age, blood pressure, duration of diabetes, medications, glycated hemoglobin (HBA1C), body mass index (BMI), ethnicity or serum creatinine. Conclusions: In diabetics with stage 1 hypertension, a 24 hour urine free cortisol to cortisone ratio >1.00 as measured by gas chromatography-mass spectrometry, independently identifies patients with a significantly higher left ventricular mass, a subset of patients known to be at a higher risk of developing cardiovascular complications.